Documentation paper: Representative survey on attitudes and knowledge about inflation and monetary policy in Germany conducted in December 2021 - Bernd Hayo (Philipps-University Marburg, School of Business and Economics, 2022)
This paper provides background information on, and basic descriptive statistics for, a representative survey of the German population conducted on my behalf by GfK in December 2021. The survey covers various topics having to do with inflation and monetary policy, including: 1) inflation perceptions and expectations, 2) interest in and subjective, as well as objective, knowledge about monetary policy, 3) attitude to and knowledge about the ECB's monetary policy reform in 2021, 4) trust in the ECB and perception of its independence, 5) importance of climate-change-related measures, and 6) an experiment evaluating whether information about the ECB's monetary policy reform in 2021 reduces people's trust in the ECB and their perception of its independence. A broad range of socio-demographic and economic indicators are collected too.
Keywords: D90; E31; E58; E71; 330; Public opinion survey; Attitudes; Inflation perception; Inflation expectation; Monetary policy; ECB's monetary policy reform in 2021; Germany